2003
DOI: 10.2298/sarh0302021m
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of arterial dopler parameters in growth restricted fetuses

Abstract: Doppler parameters enable noninvasive and direct detection of placental insufficiency and brain sparing effect, which occurs as an adaptive mechanism to chronic hypoxemia. It is of great interest if further changes of Doppler parameters, which occur after the detection of the first pathologic value, can anticipate a moment of fetal distress. We investigated growth-restricted fetuses with the brain sparing effect in the time interval between the detection of blood flow redistribution until the distress. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The mechanism for a change in the albumin profile during UPI, towards an abundance of cysteinylated albumin, is suggested by details of the transsulfuration pathway (Miles and Kraus, 2004). Initially, UPI leads to fetoplacental hypoxemia and subsequent acidosis (Mikovic et al, 2003). This ischemic environment is conducive for the formation of homocysteine.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for a change in the albumin profile during UPI, towards an abundance of cysteinylated albumin, is suggested by details of the transsulfuration pathway (Miles and Kraus, 2004). Initially, UPI leads to fetoplacental hypoxemia and subsequent acidosis (Mikovic et al, 2003). This ischemic environment is conducive for the formation of homocysteine.…”
Section: Discussionmentioning
confidence: 99%
“…According to Mikovic and colleagues, for the high-risk group, the average birth weight was 1572 grams, and the rate of maternal death was 14.3%. 17 In the current study, in the high-risk group with abnormal Doppler indices, was discovered a 1974gram average birth weight and a perinatal death rate of 3.33 percent. The diagnostic accuracy of Doppler in our study compared to other studies is depicted in (Table 5).…”
Section: Discussionmentioning
confidence: 47%
“…Furthermore, using cordocentesis in the SGA fetuses, a significant, direct correlation was found between blood oxygen deficit and increased renal artery PI . Moreover, in a study of 35 IUGR fetuses, the PI in the fetal renal arteries was significantly increased (Mikovic et al, 2003). In studies of fetal urine production, it was demonstrated that the PI in the renal artery was higher in IUGR than in AGA fetuses and that it displayed a negative correlation with the urine production rate and the amniotic fluid volume (Miura, 1991).…”
Section: Renal Artery Flow Velocity and Urine Production In Fetuses Wmentioning
confidence: 99%
“…Several studies demonstrate associations between increased impedance in the fetal renal arteries and factors suggestive of compromised fetal conditions and, in some studies, also reduced urine production rates (Mikovic et al, 2003;Miura, 1991;Stigter et al, 2001;Vyas et al, 1989). In one study, the renal artery flow-velocity wave forms were examined in normal and hypoxemic human fetuses .…”
Section: Renal Artery Flow Velocity and Urine Production In Fetuses Wmentioning
confidence: 99%